From Work Readiness To Future Competence Ai Mindset, Digital Curiosity, And Learning Agility In Indonesian Tourism Graduates - Henricus Kurniawan Elang Kusumo; Diena Mutiara Lemy; Reagan Brian (Journal of Business on Hospitality and Tourism, 2026)
This study examines the influence of AI use, digital curiosity, and learning agility on the future competencies of final-year tourism students in Indonesia, using digital self-efficacy as a mediating variable. Using a quantitative approach, data was collected from 250 students through a structured questionnaire and analyzed using SEM-PLS. The results of this study indicate that the determinants have a positive and significant influence on future competencies. Digital self-efficacy, as a mediator, fully mediated the effect of learning agility, while the other two variables had partial effects. This study contributes to tourism education by confirming the importance of a digital mindset, technological curiosity, and adaptive learning through a more reflective and experiential curriculum in preparing graduates for a future capable of utilizing AI.